ANALISIS KEDALAMAN GERUSAN LOKAL BERDASARKAN DEBIT TERUKUR (STUDI KASUS: JEMBATAN WAY BILLU) - Indri Rahmandhani Fitriana; M. Gilang Indra Mardika; Afriyanti Indi Mustari (Yayasan Nusantara Hasana Berdikari, 2025)
A threat to the sustainability of the bridge is flooding, which can cause damage, especially in the form of local erosion of the abutment. Erosion that occurs due to the presence of structures or buildings in the river is known as local erosion. This study aims to determine the maximum depth of local abrasion around the bridge abutment at the time of measured discharge using HEC-RAS software. The object of this research is the dimensions of the Way Billu Bridge with the dimensions of a new bridge after experiencing damage due to flooding on December 9, 2021. The velocity data collection method is carried out using a current meter with an average flow velocity of 0.225 m/s. The calculation of measured discharge using the mean section method resulted in a discharge of 2,413 m3/s. The sedimentation velocity produced from upstream, downstream, and river basins is 0.025 m/s, 0.017 m/s, 0.017 m/s. The results show that the depth of local erosion at the measured discharge is a total erosion depth of 0.08 m.